International Human Rights Protection: The Impact of COVID-19 Pandemic on Domestic Violence - Yordan Gunawan; Dwilani Irrynta (Yustisia, 2022)
The Corona Virus Disease 2019 (COVID-19) outbreak has impacted practically every aspect of life worldwide, particularly Asia. Governments from various States work hard to prevent and mitigate the spread by instituting multiple social distancing and lockdown measures. While those measures have been effective in containing the spread, there are other negative consequences, including the risks associated with domestic violence in the family home, whether physical, psychological, verbal, sexual, or economic violence. Subsequently, there has been a significant increase in online searches for help from intimate partner violence, according to the United Nations Population Fund (UNFPA). Moreover, the UN Women also reported that essential services, such as shelters and helplines, have exceeded their capacity. Using a normative legal research methodology that sources are obtained from secondary data, the finding shows that thousands of women living in several Asian States experienced more abuse in domestic violence and had less resilience during the pandemic. Whether national or international, the existing regulations are insufficient to prevent violence and protect victims. Thus, remote services in various sectors, including social, health, and justice, must be further developed and institutionalized by the States to overcome such issues.